SARS-CoV-2, influenza, HRSV and other respiratory pathogens during the post-COVID-19 era: Epidemic circulation in Italy in the 2023/2024 season - Serena Marchi; Valentina Salvestroni; Bianca Maria Bocci; Giovanni Guarducci; Giovanna Milano; Anna Carmina De Francesco; Emanuele Montomoli; Giovanni Bova; Andrea Camarri; Ilaria Manini (Journal of Infection and Public Health)
Objectives: This study aimed at describing the epidemiological aspects of respiratory pathogens involved in cases of severe acute respiratory infections (SARI) in Siena (Tuscany, Italy) during the 2023/2024 season. Methods: Oropharyngeal swabs were collected from enrolled patients in the University Hospital Trust of Siena. Swabs were tested by qRT-PCR for the detection of SARS-CoV-2 and other 21 respiratory pathogens, including influenza and human respiratory syncytial virus (HRSV). Swabs positive for SARS-CoV-2 and/or influenza were further analyzed by Next-Generation sequencing (NGS). Results: From January to June 2024, 138 patients diagnosed with SARI were enrolled, with an average age of 76.7 years and a frequent presence of comorbidities. Among the patients, 40 % tested positive for SARS-CoV-2, followed by 20 % positivity for influenza and 13 % positivity for HRSV. For SARS-CoV-2, variants belonging to the JN.1, EG.5 and BA.5 lineages were found. The influenza A(H1N1)pdm09 strains were found to belong to the 6B.1a.5a.2a clade, while for influenza A(H3N2), the strains belonged to two different clades (3 C.2a1b.2a.1a and 3 C.2a1b. 2a.2a.3a.1). Conclusions: This study contributes to the understanding of the spread of respiratory viruses and the genetic characteristics of SARS-CoV-2 and influenza in patients with SARI, underlining the importance of continuous surveillance.